Pengaruh Stretching Exercise terhadap Perubahan Nyeri pada Kasus Spasme Otot Upper Trapezius pada Pegawai di RS Jiwa Menur Surabaya - Tristia Nurul Hasanah; Nurul Halimah; Rachma Putri Kasimbara; Angria Pradita (Jurnal Keperawatan Muhammadiyah, 2023)
Objective:  The effect of stretching exercises to neck pain due to spasm of the upper trapezius muscle in employees at Menur Mental Hospital.Methods:  This article uses pre and post test trials conducted on 30 employees who experience neck pain due to upper trapezius spasm. This stretching exercises was carried out for 4 weeks withResults:  Stretching exercise which was carried out over 4 weeks decrease pain neck. Distinction pre-test and post-test get value Z -4.889 p.value Asymp sig 2 tailed 0,000 < 0,05. H1 received that means there is a difference significant. So it can be concluded that Stretching exercise have an effect on reducing neck pain due to spasm of the upper trapezius in employees at Menur Mental Hospital.Conclusion:  Stretching exercise have an effect on reducing neck pain due to spasm of the upper trapezius in employees at Menur Mental Hospital. The average reduction in pain in 30 health workers after 4 weeks was seen from the Wilcoxon Signed Rank test with an asymp value. sig. 2-tailed worth 0.000 <0.05.